PENERAPAN TAX PLANNING DALAM UPAYA MENEKAN PPH TERUTANG (Studi Kasus Pada PT. Transnusa Jaya Mandiri Medan) - Siregar, Nancy Mayriski; Aliah, Nur (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Tax Planning is an effort to save taxes by reducing the amount of tax liability without contradicting applicable tax laws, and in no way aims to manipulate taxation but to take advantage of opportunities with tax regulations that benefit taxpayers and do not harm the government, because the method used is legal. This research was conducted at PT Transnusa Jaya Mandiri for the purpose of implementing Tax Planning that can Minimize Corporate Income Tax Burden. As a Corporate Taxpayer, PT Transnusa Jaya Mandiri is a company engaged in heavy equipment transportation services and Jacking ProjectLogistics that is registered and has carried out its tax obligations. From the Company's financial statements and the Company's Annual Giving Letter in 2017, the results of this study show that the Tax Planning that the author applied was successful, so that there was a savings in Income Tax expenses of Rp. 26,089,981 and the Tax Planning applied was in accordance with the applicable Tax Law Regulations. It can be seen that the difference in income tax payable when applied Tax Planning which was previously Rp. 386,125,685 to Rp. 360,035,704 so that it is very clear that tax savings occurred of Rp. 26,089,981, This savings occurred because there were several costs that had been transferred as allowances and costs that were not related to taxes.